KORELASI EFIKASI DIRI DAN KECEMASAN SAAT MENYIKAPI UJIAN PADA MAHASISWA PENDIDIKAN BAHASA INGGRIS STAMBUK 21 UNIVERSITAS NEGERI MEDAN - Balqis Aulia Sukma Bangun; Hosianna Mawar Valentina; Rizky Alhusaini; Taftazani Dwilasta Ramdiaz; Theresia Christine Naibaho (Cemara Education and Science, 2025)
This research aims to determine three aspects: (1) the level of self-efficacy among students of class E, English Education Program, Stambuk 21, (2) the level of anxiety faced by these students during exams, and (3) the correlation between self-efficacy and test anxiety. This study use correlational quantitative design. The research subjects include 7 students from class E, English Education Program, Stambuk 21, selected using proportional random sampling techniques. The research was conducted in May 2024. The instruments used are self-efficacy and exam anxiety scales. The validity of the instruments was tested using the Pearson correlation coefficient formula. The data obtained were analyzed using descriptive statistics, analysis requirement tests, and the Pearson correlation coefficient with the help of Excel software on a computer. Based on the data analysis conducted, it was found that most students fall into the "Confident" category for Self-Efficacy (42.9%) and the "Calm" category for Self-Anxiety (42.9%). No students were in the "Very Confident" category for Self-Efficacy or the "Very Calm" category for Self-Anxiety. The Pearson correlation calculation showed a correlation coefficient of 0.38, indicating a weak and positive relationship between self-efficacy and self-anxiety. This weak positive relationship means that although there is a slight tendency for an increase in self-efficacy to be associated with an increase in self-anxiety, this relationship is not significant and not strong.